(untitled) (Biocenosis, 2021)
This article shines the spotlight on the need to reconnect with nature from the earliest life stages, to reinforce the affective bond with it, and generate pro-environmental behaviors in the face of the current global eco-social crisis. EmocioNatura consists of a socio-educational intervention project applied in educational centers in Costa Rica. Its purpose is for participants to know, feel and love nature, through environmental education didactic strategies with a sensorial, creative, and emotional approach.